The utilization of 3D-printed arthrodesis prostheses in the repair and reconstruction of malignant tumors in proximal humerus - Bin, Guolong; Liu, Bin; Yuan, Zhenchao; Tan, Jiachang (Frontiers in Oncology, 2025)
BackgroundThe utilization of 3D-printed arthrodesis prostheses represent a viable reconstructive option for patients who are unable to retain the deltoid muscle or axillary nerve following the resection of malignant tumors in the proximal humerus. However, there exists a limited body of literature regarding the application of this prosthetic type. In this study, we assessed the effectiveness of 3D-printed arthrodesis prostheses in the repair and reconstruction of the proximal humerus post-tumor resection. Additionally, we investigated the incidence of postoperative complications and the enhancements associated with the prostheses.Patients and methodsThis study retrospectively examined a cohort of 12 patients diagnosed with malignant tumors of the proximal humerus, who underwent reconstruction utilizing 3D-printed arthrodesis prostheses at our institution between January 2020 and December 2022. The design of the prostheses were conducted preoperatively through computer-aided design (CAD) technology, among other methods. Each patient underwent intraoperative resection of the tumor-affected segment followed by reconstruction with the 3D-printed arthrodesis prostheses. Postoperative follow-up assessments were conducted to evaluate the range of motion (ROM) of the shoulder joint, assess shoulder joint functionality, document the occurrence of complications, and analyze potential risk factors associated with these outcomes.ResultAll 12 patients underwent the procedure without complications, with an average operation duration of (172.5 ± 58.9) min (range 130-240 min). The average blood loss recorded was (450.3 ± 118.4) ml (range 200-1000 ml), and the average length of the osteotomy at the proximal humerus was (16.5 ± 1.2) cm (range 15-19 cm). The follow-up period for all patients averaged (26.2 ± 14.5) months (range 12-49 months). At the final follow-up, the average active shoulder joint abduction among the twelve patients was 75.2° ± 12.3°(range 45°-110°), while the average anterior flexion was 70.8° ± 18.4°(range 60°-125°). The average American Shoulder and Elbow Surgeons (ASES) score was 75.2 ± 6.3 points (range 63-90 points), and the Musculoskeletal Tumor Society (MSTS-93) score averaged 22.1 ± 2.5points (range 21-27 points). According to the complication classification system for post-prosthetic reconstruction proposed by Henderson, the group exhibited one case of type I, two cases of type II, two cases of type III, and two cases of type IV complications.ConclusionThe utilization of 3D-printed arthrodesis prostheses in the repair and reconstruction of malignant tumors in proximal humerus has the potential to enhance postoperative functionality. However, the prevalence of complications associated with these prostheses remains significant. Therefore, there is a pressing need for advancements in both prostheses design and surgical protocols to optimize clinical outcomes.